Research on the Regional Environmental Impact and Risk Assessment Affected by Mineral Resource Development: A Case Study of the Taojia River Watershed in Hunan - Cao, Hongying; Wang, Ziwei; Liao, Xiaoyong; Li, You; Zhu, Yongbing (Frontiers in Ecology and Evolution, 2022)
The mining and production of mineral resources can directly lead to soil and water pollution, posing a serious threat to human health. In this study, the Taojia River basin, a tributary of the Xiangjiang River, was selected as the study area. Based on the concentrations of heavy metals (As, Cd, Pb and Zn) in 653 soil/substrate samples collected from 342 points in the study area in 2013 and 2021, the changes in soil heavy metal concentrations in the region were systematically analysed to assess their environmental risks and impacts on regional environmental quality. The results showed that from 2013 to 2021, the As, Pb and Zn pollution in regional soil, tailing sand, and surface water was reduced, while the Cd pollution increased. The average soil As, Pb and Zn concentrations decreased from 3750 mg·kg-1, 2340 mg·kg-1, and 1180 mg·kg-1 to 457 mg·kg-1, 373 mg·kg-1, and 387 mg·kg-1, respectively, while the Cd concentration increased from 0.11 mg·kg-1 to 1.91 mg·kg-1; additionally, the overall distribution trend of heavy metal concentrations was high in the south, low in the north, and gradually decreased from upstream to downstream. The single evaluation index showed that the percentages of medium to heavy pollution points in the soil As, Pb and Zn were 84%, 57% and 28%, in 2013, and decreased to 38%, 37% and 25%, in 2021. The regional environmental quality was closely related to the intensity of mineral resource development. From 2000 to 2010, frequent mining development activities led to an increase in construction land and a continuous decrease in arable land, grassland and vegetation cover in the region. During 2010-2020, the area of construction land decreased, and the vegetation coverage increased. The comprehensive evaluation index showed that the overall soil pollution risk in the watershed decreased. It was showed by principal component analysis and factor analysis that mining development activities were the largest source of heavy metal pollution, in addition to mixed sources of tailings, solid waste, agriculture, and traffic emission sources. The results provide a scientific basis for the management and risk control of heavy metal pollution in the Taojia River basin.